Russkaja mental´nost´ čerez prizmu logičeskoj očerki istinno/neistinno - Romanova, T. V. (Slavistična revija, 2014)
The article looks at the content and means of expressing logical evaluations true vs. untrue in confessional memoirs of the Russian intelligentsia, seeking to define the genre status of these evaluations in modern confessional memoirs in general and see their role and function in the Russian mindset. The author describes the conceptual nature of truth- istina and truth- pravda evaluations, typical for the Russian mentality, concludes that the opposition true vs. untrue is irrelevant for the modern confessional genre, and looks at pragmatic functions of these evaluations in the Russian culture.
Keywords: 20./21.st.; 20th-21st century; conceptual analysis; confessional memoirs; resnica; ruska inteligenca; ruska književnost; ruska kultura; Russian culture; Russian intelligentsia; Russian literature; spomini; truth